Comparative Effectiveness of Corn Oil (Zea mays) with Pure Coconut Oil (Cocos nucifera L.) to Reduced Glucose Blood Levels of Alloxane Injected Wistar Rats - Khadijah Nur Al Firdausi; Sugiyanta Sugiyanta; Pipiet Wulandari (Faculty of Medicine, University of Jember, 2017)
Epidemiological studies show an increased incidence of diabetes mellitus. The initial therapy of diabetes mellitus is a diet treatment. The recommended intake of fat is a Saturated Fatty Acids (SFA) <7% and a Polyunsatturated Fatty Acid (PUFA) <10% of calories. The corn oil contains PUFA and the virgin coconut oil contains SFA as the main component. Aims of this study was to compare the effectivity of corn oil (Zea mays) and virgin coconut oil (Cocos nucifera L.) in decreasing blood glucose level in alloxane-ijnected wistar rats. This was a laboratory experiment research, used the posttest-only control design. The negative control group was wistar rats injected by aquabidest and standard feed diet (K-); the positive control group was alloxane-injected rats with standard feed diet (K+); alloxane-injected rats with standard food diet and 0.54 mL of corn oil/day for 28 days were P1 group; alloxane-injected rats with standard diet food and 0.54 mL of virgin coconut oil/day for 28 days were P2 group. Statistical analysis using the one way ANOVA test showed that the corn oil and virgin coconut oil decrease blood glucose level, but there was no significantly difference in decresing of blood glucose level between P1 and P2. This study concluded that the corn oil and the virgin coconut oil have the same effectiveness in decreasing blood glucose level in wistar rats injected with alloxane.Keywords: Corn oil, virgin coconut oil, blood glucose level, alloxane